Growth rate dalam sektor barang baku dan primer di Bursa Efek Indonesia: Mana lebih baik? - Vito Apriyanto; Febriana Louw (Akuntansi dan Teknologi Informasi, 2024)
The Sustainable Growth Rate is the maximum growth rate of a company so that it can grow without running out of funds from funding activities such as increasing shareholder capital ownership and drawing loans from creditors. This study measured, tested, and analyzed factors affecting sustainable growth. Some of the factors used in this study are leverage, profitability, and total asset turnover. This study uses objects from raw material sector companies and primary sector companies listed on the Indonesia Stock Exchange for 2018 - 2022, during which data collection was carried out using the purposive sampling method. The form of research used is associative research, a method that examines the relationship between variables, with a quantitative approach. The research data is based on secondary data, namely the company's annual financial report, which is available and has been audited by an independent auditor. Data processing uses multiple linear regression. The study results show that Leverage (DER) and Profitability (ROA) positively affect sustainable growth, providing practical insights for financial analysts and professionals in the raw material and primary sector industries. Total asset turnover (TATO) does not affect the sustainable growth rate. This study also shows that raw material sector companies have a higher sustainable growth rate than primary sector companies.